1997
DOI: 10.2337/diacare.20.10.1518
|View full text |Cite
|
Sign up to set email alerts
|

The PATHWAYS Church-Based Weight Loss Program for Urban African-American Women at Risk for Diabetes

Abstract: A weight loss program administered by trained lay volunteers was effective in producing significant and clinically meaningful weight loss among African-American women who often do not benefit from typical weight loss programs. Ongoing research is focusing on whether the weight loss can be maintained or enhanced through monthly reinforcement sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(203 citation statements)
references
References 17 publications
4
196
1
Order By: Relevance
“…The LEAN study incorporated elements common among the studies reviewed, including enrolling African American adults with overweight or obesity, embedding religious principles within the intervention, and utilizing lay health advisors (known as 'community health coaches' in LEAN) to deliver the intervention. However, few studies achieved clinically significant weight loss of >3%, [37][38][39][40] including LEAN. Our treatment fidelity data indicated that of the subset of sessions observed, the physical activity component was infrequently implemented and although the actual weight loss content was delivered adequately, there was room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The LEAN study incorporated elements common among the studies reviewed, including enrolling African American adults with overweight or obesity, embedding religious principles within the intervention, and utilizing lay health advisors (known as 'community health coaches' in LEAN) to deliver the intervention. However, few studies achieved clinically significant weight loss of >3%, [37][38][39][40] including LEAN. Our treatment fidelity data indicated that of the subset of sessions observed, the physical activity component was infrequently implemented and although the actual weight loss content was delivered adequately, there was room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…A range of services has been offered to parishioners that include screening for breast cancer (Markens, Fox, Taub, & Gilbert, 2002), prostate cancer (Collins, 1997) and heart disease prevention (Oexmann et al, 2000), smoking cessation (Schorling et al, 1997;Stillman, Bone, Levine, & Becker, 1993), diabetes management (McNabb, Quinn, Kerver, Cook, & Karrison, 1997), weight reduction (Kumanyika & Charleston, 1992), and dietary awareness (Campbell et al, 1999). Often, Black churches have collaborated with hospitals, professional associations, university-based researchers, and local and state health departments to deliver programs (DeHaven et al, 2004;Thomas, Quinn, Billingsley, & Caldwell, 1994).…”
Section: Empowerment Capacity Of the Black Churchmentioning
confidence: 99%
“…These programs established an initial successful track record Melynx & Weinstein, 1994;Pratt, 1994;McNabb et al, 1997). Their long-term success is being followed in a few cases (CDC, 2003;Yanek et al, 2001).…”
Section: For a Successful Health And Nutrition Intervention Program mentioning
confidence: 99%
“…Some study findings have included positive outcomes from church based investigations (Kumanyika and Charleston, 1992;McNabb et al, 1997), while others have not had such definitive outcomes of the role of the church (Smith, 1989). Smith (1989) examined the role of Black churches in supporting compliance with antihypertensive regimens.…”
Section: Church-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation